2013
DOI: 10.1007/s12639-013-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and histopathological finding of thin-walled and thick-walled Sarcocysts in slaughtered cattle of Karaj abattoir, Iran

Abstract: Sarcocystosis is a zoonotic disease caused by Sarcocystis spp. with obligatory two host life cycle generally alternating between an herbivorous intermediate host and a carnivorous definitive host. Some species of this coccidian parasite can cause considerable morbidity and mortality in cattle. The present study was set to investigate the prevalence of Sarcocystis spp. and type of cyst wall in slaughtered cattle of Karaj abattoir, Iran. For this purpose 125 cattle (88 males and 37 females) were investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
1
11
0
1
Order By: Relevance
“…hominis (with its thick-walled cyst) is commonly found as infectious cysts in the muscles of slaughtered cattle worldwide (80,81). Numerous studies of slaughtered cattle in Europe, South America, and Asia have demonstrated prevalence in cattle of over 40% in some countries (82)(83)(84)(85). Tissue prevalence of S. suihominis in pigs is also high, especially in Asian countries and Europe (86,87).…”
Section: Foodborne Transmissionmentioning
confidence: 99%
“…hominis (with its thick-walled cyst) is commonly found as infectious cysts in the muscles of slaughtered cattle worldwide (80,81). Numerous studies of slaughtered cattle in Europe, South America, and Asia have demonstrated prevalence in cattle of over 40% in some countries (82)(83)(84)(85). Tissue prevalence of S. suihominis in pigs is also high, especially in Asian countries and Europe (86,87).…”
Section: Foodborne Transmissionmentioning
confidence: 99%
“…It has been well established that a considerable rate of the cattle populations are infected to Sarcocystis sp in many regions of the world. The prevalence of bovine sarcocystosis is more than 90% in most regions of the world (Vangeel et al 2007;Obijiaku et al 2013;Meistro et al 2015;Nourollahi-Fard et al 2015). Several investigations have indicated that the infection rate of sarcocystosis in slaughtered animals has been ranged between 3.5% up to 100% throughout the Iran using different methods (Daryani et al 2006;Nourollahi Fard et al 2009;Nourollahi-Fard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A dificuldade de diagnosticar e evidenciar lesões macroscópicas de cistos musculares na inspeção de carnes em abatedouros faz com que este músculo venha a ser comercializado, o que não ocorre, por exemplo, com lesões provocadas por cisticercos de Taenia saginata, que são facilmente visualizadas e diagnosticadas na musculatura, uma vez que ambos parasitos têm predileção por músculos com bom suprimento sanguíneo. As observações de macrocistos de Sarcocystis na musculatura (cardíaca ou diafragma) normalmente são causadas por S. hirsuta e S. hominis, porém S. cruzi é a espécie mais frequente na musculatura de bovinos, no Brasil e no mundo (Ghisleni et al, 2006;Mounika et al, 2018;Nourani et al, 2010;Nourollahi-Fard et al, 2015). Por serem intracelulares os sarcocistos de Sarcocystis estão protegidos das defesas imunes do hospedeiro, por esta razão na maioria dos casos não ocorre uma resposta inflamatória e o achado do protozoário em lâminas de músculo estriado é comum na rotina histopatológica (Tessele et al, 2013).…”
Section: Resultsunclassified